Studi Fenomenologi Deskriptif Perempuan Penjual Sayur Keliling di Kupang berdasarkan Perspektif Psikologi Positif - Friandry Windisany Thoomaszen; Alvida Siane Rosani Bau; Windra Yunita Dulim; Greseyla Asyrea Sine (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2022)
Indonesia's 3T (Frontier, Remote, and Disadvantaged) regions are particularly prone to poverty, prejudice, and inequality for women. Therefore, having mothers working even in the informal public sector, like selling vegetables, is a type of gender equality. In the city of Kupang, it is common for mothers to sell vegetables in a traditional manner by walking around and using local items. Based on a positive psychology viewpoint, the aim of this study is to understand and describe the experiences and challenges faced by women in Kupang City, NTT who sell vegetables on the neighborhood to support their family. The research method is descriptive phenomenological study. Three individuals who fit the requirements were found; they were housewives selling goods in Kupang; they worked as greengrocers and commuted on foot; and they willingly expressed a desire to participate in the study. Thematic analysis is a technique of data processing employed. The study's findings revealed four primary themes: the experience of selling vegetables on foot; the dynamics of women who sell vegetables as they juggle several tasks; the benefits of selling vegetables on foot; and interactions with family and the community. The difficulties, exhaustion, and tension that mother suffers when selling veggies on walking are extremely real. However, despite the obstacles encountered, each subject receives a variety of benefits (in satisfying the family economy), positive meaning, and the most important is profit and psychological capital such as having positive emotions, thankfulness, perseverance, and toughness, all of which have a significant impact on happiness and psychological well-being as a human.